At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find the product of the given expression \( (x \sqrt{7} - 3 \sqrt{8})(x \sqrt{7} - 3 \sqrt{8}) \), let's follow the steps for expanding this product.
1. Rewrite the expression using the distributive property (FOIL method):
[tex]\[ (x \sqrt{7} - 3 \sqrt{8})(x \sqrt{7} - 3 \sqrt{8}) \][/tex]
2. Expand the expression:
[tex]\[ = (x \sqrt{7}) (x \sqrt{7}) + (x \sqrt{7}) (-3 \sqrt{8}) + (-3 \sqrt{8}) (x \sqrt{7}) + (-3 \sqrt{8}) (-3 \sqrt{8}) \][/tex]
3. Simplify each term individually:
- [tex]\[ (x \sqrt{7}) (x \sqrt{7}) = x^2 \cdot 7 = 7x^2 \][/tex]
- [tex]\[ (x \sqrt{7}) (-3 \sqrt{8}) = -3x \cdot \sqrt{7 \cdot 8} = -3x \sqrt{56} \][/tex]
- [tex]\[ (-3 \sqrt{8}) (x \sqrt{7}) = -3x \sqrt{7 \cdot 8} = -3x \sqrt{56} \][/tex]
- [tex]\[ (-3 \sqrt{8}) (-3 \sqrt{8}) = 9 \cdot 8 = 72 \][/tex]
4. Combine the terms:
[tex]\[ 7x^2 + (-3x \sqrt{56}) + (-3x \sqrt{56}) + 72 \][/tex]
5. Combine like terms together:
- The middle terms can be combined:
[tex]\[ -3x \sqrt{56} - 3x \sqrt{56} = -6x \sqrt{56} \][/tex]
Note that \(\sqrt{56} = \sqrt{4 \cdot 14} = 2\sqrt{14} \):
[tex]\[ -6x \sqrt{56} = -6x \cdot 2\sqrt{14} = -12x \sqrt{14} \][/tex]
6. Put everything together:
[tex]\[ 7x^2 - 12x \sqrt{14} + 72 \][/tex]
So, the result is \(7x^2 - 12x \sqrt{14} + 72\).
The correct answer is:
[tex]\[ 7 x^2 - 12 x \sqrt{14} + 72 \][/tex]
1. Rewrite the expression using the distributive property (FOIL method):
[tex]\[ (x \sqrt{7} - 3 \sqrt{8})(x \sqrt{7} - 3 \sqrt{8}) \][/tex]
2. Expand the expression:
[tex]\[ = (x \sqrt{7}) (x \sqrt{7}) + (x \sqrt{7}) (-3 \sqrt{8}) + (-3 \sqrt{8}) (x \sqrt{7}) + (-3 \sqrt{8}) (-3 \sqrt{8}) \][/tex]
3. Simplify each term individually:
- [tex]\[ (x \sqrt{7}) (x \sqrt{7}) = x^2 \cdot 7 = 7x^2 \][/tex]
- [tex]\[ (x \sqrt{7}) (-3 \sqrt{8}) = -3x \cdot \sqrt{7 \cdot 8} = -3x \sqrt{56} \][/tex]
- [tex]\[ (-3 \sqrt{8}) (x \sqrt{7}) = -3x \sqrt{7 \cdot 8} = -3x \sqrt{56} \][/tex]
- [tex]\[ (-3 \sqrt{8}) (-3 \sqrt{8}) = 9 \cdot 8 = 72 \][/tex]
4. Combine the terms:
[tex]\[ 7x^2 + (-3x \sqrt{56}) + (-3x \sqrt{56}) + 72 \][/tex]
5. Combine like terms together:
- The middle terms can be combined:
[tex]\[ -3x \sqrt{56} - 3x \sqrt{56} = -6x \sqrt{56} \][/tex]
Note that \(\sqrt{56} = \sqrt{4 \cdot 14} = 2\sqrt{14} \):
[tex]\[ -6x \sqrt{56} = -6x \cdot 2\sqrt{14} = -12x \sqrt{14} \][/tex]
6. Put everything together:
[tex]\[ 7x^2 - 12x \sqrt{14} + 72 \][/tex]
So, the result is \(7x^2 - 12x \sqrt{14} + 72\).
The correct answer is:
[tex]\[ 7 x^2 - 12 x \sqrt{14} + 72 \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.